FAKTOR-FAKTOR YANG MEMPENGARUHI AKTIVITAS PERDAGANGAN SAHAM - Reyhan Fadhil Zachary; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2021)
This research aims to analyze the factors that influence stocks trading activity in companies listed on the Indonesia Stock Exchange. Stock trading activity is measured by the number of times the company's stock transactions in a certain period. Stock that are slightly traded are called inactive stock or sleep stocks, and shares that are heavily traded are called active stocks. The independent variables used are the ratio of return on assets (ROA), debt to equity ratio (DER), and price to book value (PBV).The data used in this research is secondary data using purposive sampling method as a method of determining the sample. Sampling was taken from 45 LQ45 stocks and 45 stocks with the least transaction frequency in the Indonesia Stock Exchange, so that a research sample of 360 data (4 years) was obtained. This study uses binomial logistic regression analysis to test the research hypothesis.The results of this research successfully demonstrated that return on asset (ROA) has a significant positive effect on stocks trading activity. However, debt to equity ratio (DER) and price to book value (PBV) has no effect on stocks trading activity.